Studi Literatur: Resiliensi Gen Z lebih rendah? - Sugiyanto, Sugiyanto (Universitas Medan Area, 2025)
This study aims to determine whether there are differences in the level of resilience among Gen Z and previous generations, and to explore the reasons behind these differences. The research method employed in this study is a literature review, utilizing 10 journal articles that compare the level of resilience among Gen Z and other generations from 2018 to 2024. The results of this study show that there is a significant difference where the level of resilience of Gen Z is lower than the previous generation. Higher resilience may make a person resilient, adaptable to any environment and ready to face any changes, but lower resilience might make it difficult to bounce back from failure, hopelessness, turnover, mental disorders, depression and even commit suicide. This is due to several factors such as lack of experience, immature problem-solving solving or problem-solving. However, the potential of Gen Z is quite large in bringing about change in the academic and working world because they have different views and approaches, especially in the increasingly complex world of technology.